2013
DOI: 10.1021/jp4074398
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Assessment of Molecular Structures and Energies of Neutral and Anionic Aln (n = 2–10) Clusters

Abstract: We report the results of a benchmarking study on hybrid, hybrid-meta, long-range-corrected, meta-generalized gradient approximation (meta-GGA), and GGA density functional theory (DFT) methods for aluminum (Al) clusters. A range of DFT functionals, such as B3LYP, B1B95, PBE0, mPW1PW91, M06, M06-2X, ωB97X, ωB97XD, TPSSh, BLYP, PBE, mPWPW91, M06-L, and TPSS, have been used to optimize the molecular structures and calculate the vibrational frequencies and four energetic parameters for neutral and anionic Al(n) (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 60 publications
4
41
0
1
Order By: Relevance
“…The molecular structures of an isolated Al7 cluster, O 2 , and reaction products were optimized using M06‐2X, TPSSh, (hybrid‐meta functionals), and N12‐SX (range‐separated hybrid nonseparable gradient approximation (NGA)) with the all‐electron 6‐311+G(d) basis set. Both M06‐2X and TPSSh gave reasonable results that agree with previous experimental and high‐level theoretical data of Al clusters . B3LYP method was also used for the comparison with previous studies on the reaction of O 2 with Al clusters .…”
Section: Computational Detailssupporting
confidence: 81%
“…The molecular structures of an isolated Al7 cluster, O 2 , and reaction products were optimized using M06‐2X, TPSSh, (hybrid‐meta functionals), and N12‐SX (range‐separated hybrid nonseparable gradient approximation (NGA)) with the all‐electron 6‐311+G(d) basis set. Both M06‐2X and TPSSh gave reasonable results that agree with previous experimental and high‐level theoretical data of Al clusters . B3LYP method was also used for the comparison with previous studies on the reaction of O 2 with Al clusters .…”
Section: Computational Detailssupporting
confidence: 81%
“…So the Al 4 Si 2 demonstrates specific stability. Previous studies also revealed that Al 4 Si 4 , Al 8 Si, Al 8 Mg 2 , and Al9 clusters having 28 valence electrons show large energy gaps and enhanced stabilities . These clusters have similar oblate structures and their specific stabilities are interpreted by crystal field‐like splitting of the degenerate shells.…”
Section: Resultsmentioning
confidence: 89%
“…[40][41][42]55 Their lowest energy isomers are illustrated in Previous studies also revealed that Al 4 Si 4 , Al 8 Si, Al 8 Mg 2 , and Al − 9 clusters having 28 valence electrons show large energy gaps and enhanced stabilities. 42,43,56 These clusters have similar oblate structures and their specific stabilities are interpreted by crystal field-like splitting of the degenerate shells. Figure 2 Part of the stable adsorption systems is presented in Figure 3.…”
Section: Methodsmentioning
confidence: 99%
“…[33], Al-Au [34,35], and Pd [1] clusters. According to this figure, Al 6 and Al 13 have the maximum hardness while Al 2 and Al 9 have the minimum hardness.…”
Section: Resultsmentioning
confidence: 99%